2019
DOI: 10.1007/s10877-019-00255-6
|View full text |Cite
|
Sign up to set email alerts
|

Level of agreement of point-of-care and laboratory HbA1c measurements in the preoperative outpatient clinic in non-diabetic patients who are overweight or obese

Abstract: Implementation of point-of-care HbA1c devices in the preoperative outpatient clinic might facilitate the early diagnosis of glycemic disturbances in overweight or obese patients undergoing surgery, but validation studies in this setting do not exist. We determined the level of agreement between a point-of-care and laboratory HbA1c test in non-diabetic patients visiting the outpatient clinic for preoperative risk profiling. Point-of-care HbA1c levels were measured in whole blood obtained by a finger prick (Siem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The following results were obtained with the two models after %HbA1c value calibration: the plot of Clarke’s error grid analysis (EGA) 29 , 30 is given with the Bland–Altman analysis in Fig. 10 for the blood-vessel model and Fig.…”
Section: Results and Comparison Between Modelsmentioning
confidence: 99%
“…The following results were obtained with the two models after %HbA1c value calibration: the plot of Clarke’s error grid analysis (EGA) 29 , 30 is given with the Bland–Altman analysis in Fig. 10 for the blood-vessel model and Fig.…”
Section: Results and Comparison Between Modelsmentioning
confidence: 99%
“…They concluded that POCT-HbA1c is a potential method for diabetes screening and monitoring, especially when a rapid result is needed [ 36 ]. Moreover, the study by Raalten et al demonstrated high limits of agreement between the POCT HbA1c and the central laboratory HbA1c tests in non-diabetic, obese patients in the preoperative outpatient setting [ 37 ]. On the other hand, the recently published local experience of PSMMC hospital showed that POCT for HbA1c improved the patient’s adherence to the physician’s recommendations for HbA1c testing and higher patient satisfaction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among cases, HbA1c (%) was obtained from the electronic medical chart by abstracting the plasma HbA1c value closest to the date of study enrollment. Eligible controls included adult family members/friends of cases with HbA1c < 5.7% (measured at the time of screening by a point-of-care HbA1c [ 11 ], Siemens DCA Vantage Analyzer) and no self-reported prior diagnosis of pre-diabetes, T2DM, HIV, or TB disease. HbA1c values were categorized according to the American Diabetes Association classification with HbA1c < 5.7% considered as “normoglycemic”, HbA1c 5.7–6.4% as “pre-diabetes” and, HbA1c ≥ 6.5% as “diabetes” [ 12 ].…”
Section: Main Textmentioning
confidence: 99%